Screening of rapeseed-mustard genotypes against aphid (Lipaphis erysimi Kalt.) (Journal of Oilseed Brassica, 2026)
A field experiment was conducted to screen thirty rapeseed-mustard genotypes against mustard aphid (Lipaphis erysimi) during Rabi 2021-22 at Agricultural Research Station, Jodhpur. These genotypes consisted of seven species of rapeseed mustard i.e. Brassica juncea (10), B. rapa var. Yellow Sarson (10), B. nigra (1), B. rapa var. Toria (2), B. carinata (2), B. tournefortii (3) and Eruca sativa (2). The experimental results depicted that genotypes TM 108-1, Kranti, Bio 902, MYS 152, YSH 401 and NRCYS 05-02 were found to be resistant; genotypes viz., TM 267-3, TM 316, TM 304-1, RH 749, PM 31, GDM 4, RMYS 1, RMYS 2, RMYS 3, MYS 180, MYS 183, Jhumka, Pitambari, Tapeshwari, Bhawani, Pusa Swarna, Pusa Aaditya, MBT 27, MBT 4, and GP 115-1 were moderately resistant, while LS-FF 57, MN 1, Karantara, and RTM 1351 were found as tolerant.